Consumer Preference For Eco-Friendly Products: A Market Experiment Approach - Syaiful Amri; Yuli Astini; Dedy Febry Rachman (Dinasti Publisher, 2026)
This study examines consumer preferences for environmentally friendly products using a market experiment approach. Grounded in consumer preference theory, green consumer behavior, and the Theory of Planned Behavior, the research aims to identify key determinants influencing actual consumer choices. A quantitative experimental design was employed, involving 240 respondents, in which product attributes such as price, quality, eco-label, packaging, and environmental value were systematically manipulated. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that all variables significantly influence consumer preferences, with perceived quality and price emerging as the most dominant factors. Environmental value, eco-label, and packaging also have positive effects, although with relatively lower impact. These findings indicate that consumer decisions are primarily driven by utilitarian considerations, while environmental awareness functions as a supporting factor. The study also highlights the persistence of the attitude–behavior gap, where pro-environmental attitudes do not always translate into actual purchasing behavior. This research contributes theoretically by integrating economic and behavioral perspectives to understand sustainable consumption, and methodologically by applying a market-experiment approach to capture real choice behavior. Practically, the findings suggest that firms should prioritize product quality and competitive pricing while strengthening credible environmental communication to enhance consumer adoption of green products.